2014
DOI: 10.5306/wjco.v5.i5.1020
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptors as the novel therapeutic biomarker in non-small cell lung cancer

Abstract: Although a wide range of studies have addressed the relationship between estrogen receptor (ER) expression and prognosis in non-small cell lung cancer (NSCLC), that relationship remains controversial. This is in large part because there is no consensus on the rate of ER expression in NSCLC or on the intracellular distribution of ER expression. This suggests that establishing the relationship between ER expression and prognosis will require standardization of the antibodies used as well as the definition of a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 61 publications
(141 reference statements)
0
30
0
Order By: Relevance
“…ESR protein expression is routinely analyzed by immunohistochemistry (IHC) method. There were a number of studies employed the IHC method to explore the prognostic role of ESR in lung cancer survival and these studies were categorized by location of expression (nuclear or cytoplasm); however, according to a recent qualitative systematic review on the IHC method, contradictive results obtained from insufficient number of studies made it hard to evaluate the virtual prognostic roles of either ESR1 cytoplasm or nuclear expression in NSCLC survival [4]. The scenario of ESR2 cytoplasm expression encountered the same dilemma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ESR protein expression is routinely analyzed by immunohistochemistry (IHC) method. There were a number of studies employed the IHC method to explore the prognostic role of ESR in lung cancer survival and these studies were categorized by location of expression (nuclear or cytoplasm); however, according to a recent qualitative systematic review on the IHC method, contradictive results obtained from insufficient number of studies made it hard to evaluate the virtual prognostic roles of either ESR1 cytoplasm or nuclear expression in NSCLC survival [4]. The scenario of ESR2 cytoplasm expression encountered the same dilemma.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen receptor (ESR), with two subtypes -ESR1 and ESR2, is a vital prognostic biomarker of breast cancer [4]. Recent studies showed that both ESR1 and ESR2 were expressed in the majority of human NSCLC cell lines, which provided credible evidence on possible links between sex hormones and NSCLC prognosis [5].…”
Section: Introductionmentioning
confidence: 99%
“…As for ER‐β, immunohistocheical positivity has been frequently observed both for the nucleus and cytoplasm in lung cancer. ER‐β nuclear positivity has been related with favorable clinical outcome in most studies, whereas the opposite is true for cytoplasmic positivity . Compared with ER‐β, ER‐α shows great variability in its expression frequency.…”
Section: Lung Cancermentioning
confidence: 99%
“…Compared with ER‐β, ER‐α shows great variability in its expression frequency. ER‐α positivity is more usually observed in the cytoplasm than the nucleus in lung cancer, and ER‐α cytoplasmic positivity has been related with poor clinical outcome in NSCLC . Classically, the estrogen‐ER complex localized to the nucleus has been believed to transduce genomic signals; however, the role of cytoplasmic ERs has recently been noted, and the latter is considered important in lung cancer etiology.…”
Section: Lung Cancermentioning
confidence: 99%
See 1 more Smart Citation